Review of soluble uranium removal by nanoscale zero valent iron. (November 2016) - Jing, C.; Li, Y.L.; Landsberger, S.
Abstract: Uranium (U) has been released to surface soil and groundwater through military and industrial activities. Soluble forms of U transferred to drinking water sources and food supplements can potentially threaten humans and the biosphere due to its chemical toxicity and radioactivity. The immobilization of aqueous U onto iron-based minerals is one of the most vital geochemical processes controlling the transport of U. As a consequence, much research has been focused on the use of iron-based materials for the treatment of U contaminated waters. One material currently being tested is nanoscale zero-valent iron (nZVI). However, understanding the removal mechanism of U onto nZVI is crucial to develop new technologies for contaminated water resources. This review article aims to provide information on the removal mechanism of U onto nZVI under different conditions (pH, U concentration, solution ion strength, humic acid, presence of O2 and CO2, microorganism effect) pertinent to environmental and engineered systems, and to provide risk or performance assessment results with the stability of nZVI products after removal of U in environmental restoration. Highlights: Soluble uranium removal by zero valent iron in freshwater and waste water. Environmental restoration of uranium contaminated water. Zero valent iron nanoparticles used for environmental remediation.